Intermediate bilingual comprehension via target language priming with a short passage of discourse - Piocuda, Jorge Emilio (Kansas State University, 2015)
The revised hierarchical model assumes a strong lexical link from L2 to L1 and a strong conceptual link from L1 to L2, with both links being contingent on L2 fluency. The bilingual memory literature has discussed the role of L2 fluency in bilingual lexical and semantic retrieval; however, little is known on how priming for a target language (L1 or L2) may affect lexical and semantic access or how it is affected by L2 proficiency. The present study utilized the revised hierarchical model to examine how language priming and intermediate levels of L2 fluency affects bilingual lexical and semantic retrieval in a yes/no image/word task. 181 participants read four paragraphs of discourse to prime for a specific target language (English or Spanish) and performed a modified picture-word interference task (MPWI), in which they had to determine if image/word pairs were congruent (matched) or incongruent (did not match). The main dependent variables were accuracy and RT on the MPWI task. Additional DVs were accuracy and RT on comprehension questions over the content of the priming discourse and question type (explicit, factual, and pragmatic). Across intermediate levels of L2 fluency, those more fluent performed faster and were more accurate on the MPWI task than those less fluent. No differences were observed when the image/word pairs were congruent for English or Spanish, yet there was a language difference when incongruent for Spanish. Readers had highest percent correct for explicit questions and lowest for pragmatic questions, took longer on factual than pragmatic question, and took longer to respond when priming discourse and questions were in Spanish than when in English. The results are interpreted and discussed in terms of the revised hierarchical model, in that fluency, at least at the intermediate level, affects processing time more than accuracy. Limitations of the study, future directions, and implications for L2 educators are also discussed.
Keywords: Bilingualism; Bilingual cognition; Second language comprehension; Revised hierarchical model; Reaction time; Cognitive Psychology (0633)